Israeli’s Newspapers Coverage of Palestinian Prisoner Hunger Strike: A Peace Journalism Perspective - Awad, Samer Issa Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This study focuses on how news framing of media institutions (Israelis newspapers) affect the coverage of issues in conflict zones and set the agenda for public perceptions, especially the Palestinian Prisoners hunger strike. A total of 697 news items were analyzed from four English version of Israelis newspaper (Haartez, Jerusalem Post, Yedioth Ahronoth and Times of Israel) to investigate how they portray the other (Palestinians prisoners) through an action (hunger strike) during a period of time (2012-2017) through a peace journalism perspective. Using Ersoy’s peace journalism coding schema, the study found that the total news from four newspapers portrayed the issues with negative frames (n = 542; 77.8%) while some of the news appeared to have portrayed the hunger strike issues in more positive frames (n = 155; 22.2%). However, the study concludes that tendency of the Israeli media toward the other in the hunger strike were negative in framing the Palestinian prisoners as “threat” and “terrorists” instead of being balanced while they are covering humanitarian issue in conflict zone. It therefore, recommends the need conduct more research that focus on advocating the use of peace journalism approach in the coverage of conflict issues. Keywords: Palestinian Prisoner, Hunger Strike, Agenda Setting Theory, Framing Theory, Peace Journalism Theory, Israeli Media, Peace Media, War Coverage, Conflict Zone.

ÖZ: Bu çalışma, media kuruluşlarının (İsrail gazeteleri) haber çerçevelerinin, özellikle Filistinli mahkumların açlık eylemiyle ilgili olarak, çatışma alanındaki olayların kapsamını ve kamu algısı için oluşturulan gündemin nasıl etkilendiği üzerine yoğunlaşmıştır. Araştırmada, İngilizce yayın yapan dört İsrail gazetesinin (Haartez, Jerusalem Post, Yedioth Ahronoth and Times of Israel) toplamda 697 haberi üzerinden, Filistinli mahkumların 2012-2017 arasındaki açlık eylemlerinin nasıl tanımlandığı barış gazeteciliği yönünden incelenmiştir. Ersoy’un (There should be date) barış gazeteciliği kodlama şeması kullanılarak, çalışmada yer alan dört gazetenin olayları olumsuz çerçeveden (n=542; 77.8%) betimlediği ve bazı haberlerde de (n=155; 22.2%) açlık eylemini olumlu olarak betimlendiği bulgulanmıştır. Bununla birlikte, İsrail medyasının açlık eylemleri üzerinden yöneliminin, çatışma alanında insani durumlar kapsamında dengeli olmak yerine Filistinli mahkumları ‘tehdit’ ve ‘terörist’ gibi olumsuz çerçeveden ifade ettiği sonucuna ulaşılmıştır. Bu nedenle, barış gazeteciliği yaklaşımının çatışma konularının kapsamı içinde kullanımını savunmaya odaklanan daha fazla araştırma yapılmasını önerilmektedir. Anahtar Kelimeler: Filistinli Mahkum, Açlık Eylemi, Gündem Belirleme Teorisi, Çerçeveleme Teorisi, Barış Gazeteciliği Teorisi, İsrail Medyası, Barış Medyası, Savaş Kapsamı, Çatışma Alanı.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2020. Supervisor: Assoc. Prof. Dr. Metin Ersoy.
Keywords: Communication and Media Studies; Mass Media and Peace--Peace Journalism; Palestinian Prisoner; Hunger Strike; Agenda Setting Theory; Framing Theory; Peace Journalism Theory; Israeli Media; Peace Media; War Coverage; Conflict Zone